Efficacy and safety of sotatercept across ranges of cardiac index in patients with pulmonary arterial hypertension: a pooled analysis of PULSAR and STELLAR - Gomberg-Maitland, Mardi; Badesch, David B.; Gibbs, J. Simon R.; Grünig, Ekkehard; Hoeper, Marius M.; Humbert, Marc; Kopeć, Grzegorz; McLaughlin, Vallerie V.; Meyer, Gisela; Olsson, Karen M.; Preston, Ioana R.; Rosenkranz, Stephan; et al. (The journal of heart and lung transplantation, 2025)
Background - This analysis examined the effects of the activin signaling inhibitor, sotatercept, in pulmonary arterial hypertension (PAH) subgroups stratified by baseline cardiac index (CI). - Methods - Pooled data from PULSAR (N=106; NCT03496207) and STELLAR (N=323; NCT04576988) were analyzed using 2 different CI thresholds, <2.0 and ≥2.0liter/min/m2 as well as <2.5 and≥2.5 liter/min/m2. Median changes from baseline at week 24 were evaluated using Hodges-Lehmann estimator and least squares (LS) means, with 95% confidence intervals and p-values (significance: p=0.05). Categorial endpoints and time-to-clinical worsening were analyzed by Cochran-Mantel-Haenszel and Cox model respectively. - Results - Of 429 participants, 51 had CI <2.0 and 378 ≥2.0liter/min/m2, while 179 had CI <2.5 and 250 ≥2.5liter/min/m2. Sotatercept significantly improved median 6-minute walk distance (range: 33.9 to 63.7m: p<0.001), pulmonary vascular resistance (range: −202.8 to −395.4 dyn•s•cm−5; p≤0.002), and N-terminal pro-B-type natriuretic peptide (range: −317.3 to −1,041.2pg/ml; p<0.001) across subgroups. LS means showed reductions in pulmonary and right atrial pressures, decreased right ventricular size, and improved tricuspid annular plane systolic excursion/systolic pulmonary artery pressure. Sotatercept delayed time to first occurrence of death or a worsening event for CI ≥2.5 (hazard ratio [HR] 0.12; p<0.001), ≥2.0 (HR 0.13; p<0.001), and <2.5 (HR 0.21; p<0.001) liter/min/m2. Improvements were observed in WHO functional class (all p<0.050) and ESC/ERS risk scores (all p<0.001). - Conclusions - Sotatercept demonstrated consistent efficacy and safety across CI subgroups, supporting its use in PAH patients irrespective of baseline cardiac hemodynamics.